Prolegomena to a Timely Reading of Zen Master Hakuin: his Political Critique, Moral Attitude, and Social Engagement Against the Abusive Authority of the Tokugawa Shogunate - Matsubara, Masaki (Acta Orientalia Vilnensia, 2004)
The purpose of this paper is to examine the political attitudes of Zen master Hakuin Ekaku (1686-1769) against the abusive power of the Tokugawa-shogunate’s authority. It first reconsiders briefly the received views of Hakuin as the reviver of the contemporary Japanese Rinzai Zen tradition. It suggests that the hitherto dominant interpretations of Hakuin as a powerful religious icon of the tradition have been crafted by Zen authorities to maintain a conservative, elite Zen system. It then examines and reevaluates Hakuin’s political critiques that have been heretofore overlooked by scholars and intellectuals, focusing on some of his neglected works, particularly the Hebiichigo as well as others. In particular, it considers his moral attitude, political critique of abusive power, and social engagement against political authority. Why has the established Zen hierarchy ignored these political aspects of Hakuin’s work? How can a new reading of Hakuin’s critiques of power be used to reexamine the course of the tradition’s history up to the present? How is it possible to map a new understanding of Hakuin that is appropriate for today? This paper explores not only the contents of these neglected treatises and the possible reasons these writings were suppressed, but more importantly, it locates the preCise meaning of Hakuin today.